Fundamentals of entrepreneurship (ENT300) : Proposal Borneo home stay / Dzarul Harith Osman … [et al.] - Osman, Dzarul Harith; Uteng, Muhammad Fazdli; Jelimang, Norita; Francis, Caroline (2014)
Our company is Borneo home stay. The business has been decided on the form of partnership. Each of us contributes certain amount of capital as agreed in our agreement. Our main business activity is to give services and to support our local product at Santubong area. We will open our company at Taman Sri Sarawak, Jalan Padungan, Kuching, Sarawak and our business will be commence by 1st June 2014. All four of us have to agreed to participate in all the business management that will establish that is Dzarul Harith Osman as a General Manager/ Administration Manager, Caroline Anak Francis as a Financial Manager, Norita Anak Jelimang as a Marketing Manager, and Mohammad Fadzli Uteng as a Operational Manager.